Temporal (monthly) RGB orthomosaics from Episkopi Beach (north Crete, Greece) using the DJI Mavic Air 2 drone - Alevizos, Evangelos (PANGAEA, 2024)
These orthomosaics resulted from drone imagery acquired quasi-monthly between November-2022 and November-2023, using a DJI Mavic Air 2, equipped with a 1/2 CMOS sensor, flying along a 2 km segment at Episkopi Beach. Image capture occurred manually, hovering above each waypoint and camera sensor facing at the nadir. The flight altitude was different at each survey ranging between 290-360 meters above sea-level for capturing a large area of the surf zone and part of the onshore area, thus assisting in producing large-scale orthomosaics from raw drone imagery. The camera sensor records standard RGB images with 12Mp pixel resolution, resulting in a ground sample distance (GSD) of approximately 20 cm. Images were taken using a neutral density (ND-256) filter and long shutter speeds for improved image quality and eliminating image noise due to wave-focusing on the seafloor. The shutter speed was set to 1.3-2 seconds, ISO sensitivity was set to 100 and image overlap was determined visually by having a prominent ground feature captured in three consecutive images along the flight path. Image acquisitions occurred when the sea state was calm (<0.2m significant wave height), sun elevation was <30 degrees, or cloud coverage was low and homogeneous for minimizing sun-glint noise. Drone images were processed in Pix4D proprietary software for obtaining a set of RGB orthomosaics. Initially, the cameras' positions were reconstructed using SfM processing and camera-specific geometric corrections were applied. Following, bundle adjustment and georeferencing were performed using the navigation metadata of imagery. Camera-specific radiometric corrections, including sensor bias, sensitivity, gain settings, exposure settings and lens vignette effects, were also applied using Pix4D software. The output orthomosaics cover a coastal area that is ~2 km long and more than 200 meters wide. Each of the original RGB orthomosaics was georeferenced in QGIS using a reference orthomosaic (from 9.May.2023) that is highly aligned with GoogleEarth basemap, and a set of 7-10 control points. The root-mean-square error (RMSE) between these points varied from 0-1.5 m. However, horizontal differences up to 4 m were found by visually examining independent target features between each mosaic.
Keywords: Aerial Images; Bathymetry; Beach; bedforms; Coastal; Drone; Geomorphology; Mediterranean; morphodynamics; Nearshore; RGB; Seafloor images